Financial Inclusion, Risk Management Practices, and SME Performance: A Mixed Methods Study of Mediation Effects in Emerging Economies - Nira Dewi Susanti; Andika Benu; Fransisca Ursula Yakomina Lau Yalla; Nurlia Nurlia (Management Study Program, Universitas Kristen Indonesia Paulus, 2026)
This study examines the relationship between financial inclusion, risk management practices, and SME financial performance using an explanatory sequential mixed methods approach. Quantitative data were collected from 140 SME owners in Makassar and Balikpapan and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM), followed by qualitative interviews to provide deeper insights into the findings. The results reveal that financial inclusion does not have a significant direct effect on SME financial performance. However, it has a strong positive effect on risk management practices, which in turn significantly improve financial performance. Furthermore, risk management practices fully mediate the relationship between financial inclusion and SME performance. Qualitative findings support these results, indicating that access to financial services alone is insufficient to enhance performance without adequate managerial capabilities in managing financial risks. The study contributes to the literature by integrating the Resource-Based View and Dynamic Capability Theory, highlighting the importance of internal capabilities in leveraging external financial resources. Practically, the findings suggest that policymakers should complement financial inclusion initiatives with capacity-building programmes in risk management to achieve sustainable SME performance.